Korelasi Antara Paparan Model Berkulit Tan di Instagram @Lafiye Dengan Rasa Percaya Diri Followers - Hana Naurah Kafidani; Sumardjijati Sumardjijati (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
Beauty standards in Indonesia that emphasize fair skin often make women with tanned skin feel less confident. This study aims to determine the relationship between exposure to tanned models on the Instagram account @Lafiye and the self-confidence of female followers with similar skin tones. An explanatory quantitative approach was used in this study, with data collected through an online questionnaire from 100 female respondents with tanned skin who follow the account @Lafiye. Variable X was measured using indicators of frequency and duration of exposure, while variable Y included self-confidence, optimism, and objectivity. The analysis was conducted using the Spearman Rank correlation test. The results showed that there was no significant relationship between the two variables, with a correlation value of r = 0.087 and a significance of p = 0.392. These findings indicate that the visual representation of tanned models on social media is not strong enough to influence overall self-confidence. This study recommends that brands should not only rely on visual appearance, but also include narratives that support self-acceptance and diversity as part of their communication strategy.